Posted by **Jen** on Tuesday, January 30, 2007 at 2:06pm.

Express

P(x) = x^5 + 6 x^3 - x^2 - 2x + 5

as the sum of an odd function and even function.

Podd(x)=x^5 +6x^3- 2x

Peven(x)= -x^2 + 5

## Answer This Question

## Related Questions

- odd and even functions - Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x...
- Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...
- math - I know It's probably an easy question but I don't know remember how to do...
- Math - If f and g are functions defined for all real numbers, and f is an odd ...
- Calculus, check my answer, please! 1 - Did I get this practice question right? 1...
- Algebra - Confused Please Help! Thanks! Let f(x) = 1 – 3x^2. Which of the ...
- Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Please give us a ...
- Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...
- Math - Let f and g be two odd functions. Prove that: a) f + g is an odd function...
- Trigonometry - 1. Using the definitions of odd and even functions, explain why y...

More Related Questions